Ameliorating loneliness through Cognitive Stimulation Therapy and the role of baseline loneliness in predicting cognitive, behavioural and psychological benefits in people with dementia - Domenicucci, Riccardo; Carbone, Elena; Piras, Federica; Borella, Erika (Frontiers in Psychology, 2025)
IntroductionWe examined whether Cognitive Stimulation Therapy (CST) would ameliorate loneliness and its social and emotional components in the short and long-term among people with mild-to-moderate dementia. The role of loneliness and its dimensions, as individual characteristics, in explaining short- and long-term cognitive, behavioural, and psychological CST benefits was also assessed.Materials and methodsPeople with dementia, either receiving the Italian adaptation of CST (CST group: n = 68) or treatment-as-usual (control group: n = 47), were selected from a previous multicenter controlled clinical trial on CST efficacy. They completed the de Jong Loneliness Scale along with measures of general cognitive functioning, language, mood, behaviour, and quality of life before CST intervention, immediately after the treatment, and 3 months later.ResultsA specific short-term reduction in emotional loneliness was found for the CST group compared to controls but it was no longer observable at follow-up. Baseline total loneliness helped explain short-term improvements in depressive symptoms and short- and long-term benefits in quality of life. Specifically, lower baseline social loneliness accounted for short-term decrease in depressive symptoms, whereas higher baseline emotional loneliness explained short- and long-term benefits in quality of life.ConclusionCST can reduce emotional loneliness in PwD, albeit in the short-term. Moreover, individual dispositions in terms of social and emotional loneliness seem to have a modest influence on CST’s benefits in mood and quality of life. Loneliness in PwD should be systematically addressed in psychosocial interventions, also to direct individuals who are more predisposed to derive benefits from approaches such as CST.